PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN JASA GOJEK ONLINE DI YOGYAKARTA - Hendriarto Hendriarto; Yenni Kurnia Gusti (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
This study aims to determine how much influence price and service quality on the customer satisfaction of Gojek in Yogyakarta, either partially or simultaneously. The population in this study were Gojek service users in Yogyakarta, with a sample of 100 respondents. Sampling using a purposive sampling technique. Data collection techniques using a questionnaire. The data analysis technique used is multiple linear regression. The validity test shows that the statement in this study is valid, while the reliability test using Cronbach Alpha is declared reliable. The results show that: (1) Price and service quality simultaneously affect Gojek customer satisfaction. (2) Price and service quality partially affect Gojek customer satisfaction. Service quality is the most influential and dominant variable on customer satisfaction of Gojek in Yogyakarta so that this research can be useful for companies to continue to improve the quality of their services, in order to achieve customer satisfaction.